2021
DOI: 10.1186/s12890-021-01708-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the timing of bronchoscopic alveolar lavage on children with adenovirus pneumonia: a comparative study

Abstract: Background Adenovirus pneumonia is prone to severe clinical and imaging manifestations in children. Bronchoscopic alveolar lavage (BAL) is an important adjunctive therapy for patients with severe imaging findings. The study aimed to evaluate the effect of the timing on the efficacy of bronchoalveolar lavage in children with adenovirus pneumonia. Methods This study included 134 patients with adenovirus pneumonia treated with BAL at Guangzhou Women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…No AdV was detected, however, and the fungal population was surprisingly low. Conversely, this virus was found to be more common in the research conducted by Ma et al and Huang et al [14,17,18], especially with the development of pathogenic metagenomic technology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…No AdV was detected, however, and the fungal population was surprisingly low. Conversely, this virus was found to be more common in the research conducted by Ma et al and Huang et al [14,17,18], especially with the development of pathogenic metagenomic technology.…”
Section: Discussionmentioning
confidence: 95%
“…These factors contribute to poor tolerance of BAL and increase the risk of complications. A recent study of AdV pneumonia also showed that there was no statistically significant difference in the duration of fever and hospital stay between patients in the severe group who received BAL in the early stages and those who received BAL in the later stages [18]. It is even speculated that receiving BAL in the early stages may increase the chance of mechanical ventilation and the occurrence of surgical complications in severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that longer duration of fever (especially more than 10.5 days), acute respiratory failure, require invasive mechanical ventilation in the acute phase are more likely to develop BO [17,18]. Airway in ammation in children with BO increased, and the total number of white blood cells, neutrophil count, IL-1β, IL-6, IL-8 and TGF-β in the induced sputum were signi cantly increased [19], research in China reported that early BAL in severe HAdV pneumonia might not shorten the course of the disease or improve prognosis and may even increase the risks of mechanical ventilation and BAL complications [20], therefore, during the acute stage treatment of severe HAdV pneumonia complicated with encephalitis/ encephalopathy, the use and course of glucocorticosteroid and whether BAL therapy should be more aggressive to reduce airway in ammation and avoid progression to BO need further prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy combined with bronchoalveolar lavage can not only clamp the blocked mucus plug out of the small bronchi and effectively ease the clinical symptoms of children with pulmonary consolidation and atelectasis but also obtain alveolar lavage fluid, which is conducive to improving the detection efficiency of pathogens, adjusting drug usage, shortening the course of the disease, and reducing the hospitalization time needed ( 79 ). However, some studies have shown that BAL in mild cases can reduce the condition, while there is no significant difference in the incidence of pulmonary sequelae and death cases between the group receiving BAL in the early and late stages of SAP ( 114 ).…”
Section: Therapymentioning
confidence: 99%